The geology and geochemistry of granitoid at Kg. Ulu Geh, Kuala Krai, Kelantan - Sahliziyan Ramli (2018)
Geological research including lithology, geological structure, stratigraphy, geomorphology and petrology in Kg. Ulu Geh, Kuala Krai, Kelantan. The study area has longitude of 102° 13" 35°’ to 102° l6“20” and the latitude of 05° 38" 45” to 05° 41" 30” . The objective in study area is to produce geological map of the study area and analyses the geochemistry of granite at Kg. Ulu Geh, Kuala Krai, Kelantan. There are two methodologies that have been used in this project which are mapping and laboratory work. For geological mapping, the rock found is granite and andesite. The ﬁeldwork also needed observation of lithology and drainage pattern which consists of dendtitic and parallel pattern. Besides, landfonn type is mostly covered by hilly area. Granitoid that found in study area is mainly quartz syenite. This genesis of granitoid was generated at zones of collision between continents and oceanic crust where is continents were amalgamated. Granitoid is the main components of continents that are one of the oldest known rocks. The main evidences were provided at the geological history based on the growth and evolution of the continents throughout the time. Regionally, the andesite is actually the intrusion of the granitoid. The laboratory analysis is included the petrography analysis and X-ﬂuorescence for geochemistry analysis. The study of quartz syenite can be concluded through detail petrographic that this area generally consists mineral such as quartz, alkali feldspar, biotite, hornblende, plagioclase and pyroxene.